ANALISIS CITRA MEREK DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI MAKANAN ONLINE (Studi Kasus Pelanggan Aplikasi Go Food, Grab Food, Shopee Food) - Yunita Indriany; Sri Hastuti; Dwi Indrisetno P.V (POLITEKNIK LP3I JAKARTA, 2022)
This study aims to determine and analyze the effect of brand image and consumer attitudes on purchasing decisions, either partially or simultaneously on the Online Food Application (Go Food, Grab Food, Shopee Food). The type of research used is the quantitative approach. The population in this study are users of online food applications (Go Food, Grab Food, Shope Food). The sampling technique used was purposive sampling method, namely that the data was selected based on certain criteria. Based on the predetermined criteria, the sample of 130 respondents was obtained. The data analysis method used was multiple linear regression analysis (SPSS). The results of this study indicate that: (1) Brand Image (X1) partially has the significant effect on purchasing decisions as it is evidenced by the results with a significance t of 0.001; (2) Consumer Attitudes (X2) partially have the significant effect on purchasing decisions, this is evidenced by the results of the significance t of 0.000; Simultaneously, Brand Image, and Consumer Attitudes have the significant effect on purchasing decisions as it is evidenced by the results of the significance F of 0.000 which is less than 0.05.Keywords: Brand Image, Consumer Attitude, Purchase Decision